The Plasma Kallikrein–Kininogen Pathway Is Critical in the Pathogenesis of Colitis in Mice - Wang, Bo; Yang, Aizhen; Zhao, Zhenzhen; He, Chao; Liu, Yuanyuan; Colman, Robert W.; Dai, Jihong; Wu, Yi (Frontiers in Immunology, 2018)
The kallikrein-kinin system (KKS) consists of two serine proteases: prekallikrein (pKal) and factor XII (FXII), and a cofactor, high-molecular-weight kininogen (HK). Upon activation of the KKS, HK is cleaved to release bradykinin. Although the KKS is activated in humans and animals with inflammatory bowel disease (IBD), its role in the pathogenesis of IBS has not been characterized. In the present study, we determined the role of the KKS in the pathogenesis of IBD using KKS-knockout mice. In two colitis models, induced by dextran sulfate sodium (DSS) and 2,4,6-trinitrobenzene sulfonic acid (TNBS), mice deficient in HK, pKal, or the two bradykinin receptors displayed attenuated phenotypes including body weight loss, disease activity index, colon length shortening, reduced histological scoring, and increased colonic production of cytokines. Infiltration of neutrophils and inflammatory monocytes in the colonic lamina propria was reduced in HK-deficient mice. Reconstitution of Kng1-/- mice with HK recovered their susceptibility to DSS-induced colitis, increased IL-1β levels in the colon tissue, and increased the bradykinin concentration in the plasma. In contrast to the phenotypes of other KKS-knockout mice, mice lacking FXII had comparable colonic inflammation to that observed in wild-type mice. Bradykinin production was significantly increased in the plasma of wild-type mice in the DSS-induced colitis model, suggesting activation of the KKS. In vitro analysis revealed that DSS-induced pKal activation, HK cleavage, and bradykinin release in the plasma were prevented by the absence of pKal and the inhibition of Kal. Unlike DSS, TNBS did not induce HK cleavage. Collectively, our data strongly suggests that Kal, acting independently of FXII, contributes to experimental colitis by promoting bradykinin release from HK.